Political leadership and Nigeria’s image crisis - Aleyomi, Michael B.; Mohamad Zaini Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2018)
The myriads of socio-economic and political challenges that bedeviled Nigeria have been the crux of much debate. The pendulum has swung from one extreme to the other throughout history. However, the debate as to the impact of these challenges on external perception about Nigeria is still ongoing. In spite of vast literature on the Nigerian project and the country’s potentials for greatness, all seem to be sound and fury without a clear cut line of action towards addressing Nigeria’s plummeting image. This is the focus of the current effort. The paper examines the salient motivations for Nigeria’s ‘falling’ image and external perceptions on Nigerians in the context of political leadership. Applying both primary and secondary methods of data collection which were qualitatively analyzed the study discovers that the fundamental factor dampening Nigeria’s image is a failure of leadership and irresponsible followership resulting from corruption, diplomatic frailties, lack of political will to ensure dignity and integrity, among other manifestations. While the paper underscores some leadership efforts to building a positive image, it argues that the instrumentality of implementation is in a state of vacillation. Thus, the paper concludes that corruption and failure of leadership are responsible for Nigeria’s image crisis. Hence, the paper recommends, among others, that there is need to build a symbiotic relationship between the Nigerian leadership and citizenship upon the infallible foundations of trust, integrity, patriotism and an unyielding spirit of nationalism, with the aim of establishing strong structures and institutions. This requires the culture of good governance.